CEB-01 membrane loaded with SN-38 for local post-resection control and metastasis reduction in preclinical pancreatic cancer models - Anna Huguet Ninou; Pablo Caruana; Luc Marti; Jose Tornero; Ester Lopera de Llanos; Francesc Cano Casas; Noa De la Fuente; Fátima Aguilar-del Castillo; Carlos García-Sanchez; Carmen Cepeda-Franco; Javier Padillo-Ruíz; María Virtudes Céspedes (Drug Delivery and Translational Research, 2025)
Pancreatic cancer (PC) is an aggressive malignancy with extremely poor prognosis, in which resection surgery remains the only therapeutic option with curative intent. Patients often present with locoregional metastases in lymph nodes, peritoneum and liver at diagnosis (~ 50–60% of patients), precluding the possibility of surgical resection. In addition, majority of patients develop tumor recurrence after surgery, which can be local or metastatic, in both cases negatively affecting survival outcomes. Irinotecan has proven effective as an adjuvant setting after surgery and currently used in chemotherapeutic combination regimes for the management of PC. The extreme low solubility of irinotecan’s active metabolite, 7-ethyl-10-hydroxycamptothecin (SN-38), along with its instability at physiological pH, creates significant challenges for SN-38 systemic administration as a free drug, despite its much greater potency compared to irinotecan. CEB-01 is a novel formulation of SN-38 in the form of a biodegradable nanofiber Poly (Lactic-co-Glycolic Acid) (PLGA) membrane. Implanted in the PC surgical bed, CEB-01 releases SN-38 in a prolonged manner for tumor growth control. Using in vivo pancreatic models, CEB-01 shows statistically significant reduction of postoperative tumor growth at local concentrations of SN-38 between 25 and 50 µg/cm 2 , both as monotherapy and in combination with chemotherapy (5-FU 30 mg/kg and 90 mg/kg leucovorin), in MIA PaCa-2 and metastatic Panc-1 pancreatic xenograft models. In addition, CEB-01 shows statistically significant effect on metastatic control, by reducing the number of metastases in liver, lymph nodes, and peritoneum in treated animals. Overall, no systemic toxic effects or changes in body weight were observed, confirming that CEB-01 shows a tolerable profile after post-surgical resection in in vivo models of PC. In conclusion, CEB-01 is a feasible drug delivery strategy for the local release of SN-38 as an add-on adjuvant to current PC treatments, strategy that could potentially reduce systemic side effects compared to intravenous administration of irinotecan. Graphical abstract

Aspartic proteases from Silybum marianum: different plant-specific inserts, different destinations - M. Laura Colombo; Agustina Fernández; Constanza S. Liggieri; Pablo Tornero; Laura S. Bakás; Sandra E. Vairo-Cavalli (Planta, 2025)

Hormonal Regulation of Ovule Initiation in Arabidopsis - Daniela Barro-Trastoy; Maria Dolores Gomez; Pablo Tornero; Miguel A. Perez-Amador (Journal of Plant Growth Regulation, 2024)
As seed precursors, ovules are fundamental organs during the plant life cycle. Decades of morphological and molecular study have allowed for the elucidation of the complex and intricate genetic network regulating ovule development. Ovule and seed number is highly dependent on the number of ovule primordia that are determined from the placenta during early pistil development. Ovule initiation is positively regulated by the plant hormones auxins, cytokinins, and brassinosteroids, as well as negatively regulated by gibberellins. Each hormone does not act independently; multiple points of hormonal crosstalk occur to coordinately regulate ovule primordia initiation. In this review, we highlight the roles of these hormones and their interactions in the genetic and hormonal network co-regulating ovule initiation in Arabidopsis.

Livestock management at the Late Iron Age site of Baltarga (eastern Pyrenees): an integrated bio-geoarchaeological approach - Lídia Colominas; Marta Portillo; Jordi Morera; Joan Oller; Anna Berrocal-Barberà; Abel Gallego-Valle; Oriol López-Bultó; Chiara Messana; Joaquim Sisa-López de Pablo; Carlos Tornero; Oriol Olesti (Archaeological and Anthropological Sciences, 2023)
Despite the important role of livestock farming amongst Iron Age communities living in mountain regions, there is little information about livestock management, and particularly stabling practises, breeding systems, and grazing/foddering patterns. The study of the ground floor of Building G in Tossal de Baltarga has provided valuable insights into these important issues and has given us a better understanding of the social and economic patterns involved in all these livestock activities. It revealed the existence of a stable from the Late Iron Age, thanks to unique in situ finds of the stabled animals, including four sheep, a goat, and a horse, in addition to a range of organic remains preserved by fire and penning deposits. It is the first documented to date in the northeastern Iberian Peninsula. Through an integrated bio-geoarchaeological approach, combining a range of analytic procedures, including osteology, dental microwear, stable isotopes, phytoliths, dung spherulite analyses, and thin-section micromorphology, for the first time, this study has provided new, high-resolution evidence of livestock management strategies. Specifically, the research shed light on animal penning and feeding practises, revealing variable herbivorous regimes between species, the practise of seasonal movements, and the possible use of fodder as the main dietary regime of the animals stabled there. At the same time, the Baltarga case-study illustrates an indoor production unit that could reveal possible private control of some domestic animals in the Pyrenean Late Iron Age.

A cryptic variation in a member of the Ovate Family Proteins is underlying the melon fruit shape QTL fsqs8.1 - Cecilia Martínez-Martínez; Maria José Gonzalo; Pablo Sipowicz; Manuel Campos; Irene Martínez-Fernández; Carmen Leida; Mohammed Zouine; Konstantinos G. Alexiou; Jordi Garcia-Mas; María Dolores Gómez; Pablo Tornero; Miguel Ángel Pérez-Amador; et al. (Theoretical and Applied Genetics, 2022)
Key message The gene underlying the melon fruit shape QTL fsqs8.1 is a member of the Ovate Family Proteins. Variation in fruit morphology is caused by changes in gene expression likely due to a cryptic structural variation in this locus. Abstract Melon cultivars have a wide range of fruit morphologies. Quantitative trait loci (QTL) have been identified underlying such diversity. This research focuses on the fruit shape QTL fsqs8.1 , previously detected in a cross between the accession PI 124112 (CALC, producing elongated fruit) and the cultivar ‘Piel de Sapo’ (PS, producing oval fruit). The CALC fsqs8.1 allele induced round fruit shape, being responsible for the transgressive segregation for this trait observed in that population. In fact, the introgression line CALC8-1, carrying the fsqs8.1 locus from CALC into the PS genetic background, produced perfect round fruit. Following a map-based cloning approach, we found that the gene underlying fsqs8.1 is a member of the Ovate Family Proteins (OFP), CmOFP13, likely a homologue of AtOFP1 and SlOFP20 from Arabidopsis thaliana and tomato, respectively. The induction of the round shape was due to the higher expression of the CALC allele at the early ovary development stage. The fsqs8.1 locus showed an important structural variation, being CmOFP13 surrounded by two deletions in the CALC genome. The deletions are present at very low frequency in melon germplasm. Deletions and single nucleotide polymorphisms in the fsqs8.1 locus could not be not associated with variation in fruit shape among different melon accessions, what indicates that other genetic factors should be involved to induce the CALC fsqs8.1 allele effects. Therefore, fsqs8.1 is an example of a cryptic variation that alters gene expression, likely due to structural variation, resulting in phenotypic changes in melon fruit morphology.

Quantitative genetic analysis of salicylic acid perception in Arabidopsis - Albor Dobón; Juan Vicente Canet; Lorena Perales; Pablo Tornero (Planta, 2011)